Treatment of Degenerative Lumbar Spondylolisthesis by Tongdu Bushen Acupuncture, Intradermal Acupuncture, and Moxibustion Integrated Therapy Combined with Core Muscle Training Program: Study Protocol for a Randomized Controlled Clinical Trial. (23rd March 2022) - Song, Xiaolei; Qi, Shikui; Gao, Jing; Ruan, Xiaodi; Yin, Shuai; Wu, Mingli; Fu, Wenbin
Abstract : Background . Degenerative lumbar spondylolisthesis (DLS), one of the most common causes of low back pain, is defined as the displacement of a vertebral body over the lower vertebral body with degenerative changes and the absence of fracture or defect in the vertebral ring. This disease is a common and frequently occurring disease. Currently, there are many clinical treatment methods, but there is no specific method, and most of them have the characteristics of slow effect and easy recurrence. Objective . The objective of this study is to summarize and analyze the effects of treatment of degenerative lumbar spondylolisthesis by Tongdu Bushen acupuncture, intradermal acupuncture, and moxibustion integrated therapy combined with core muscle training program (CMT) on the improvement of pain degree and dysfunction index, as well as the gait characteristics. Methods . 120 patients with DLS will be recruited and randomly divided into two groups using electroacupuncture combined with the CMT group as the control group. Visual Analogue Scale (VAS), Oswestry Disability Index (ODI), and Japanese Orthopedic Association score (JOA) will be used for evaluation. The spatiotemporal and kinematics parameters in gait analysis, as well as the ability of lumbar muscle contraction, fatigue resistance, relaxation, and coordination of lumbar muscle in surface electromyography (sEMG), will be used as objective observation indexes to observe the effectiveness of Tongdu Bushen acupuncture, intradermal acupuncture, and moxibustion integrated therapy combined with CMT. Discussion . Tongdu Bushen acupuncture, intradermal acupuncture, and moxibustion integrated therapy is a traditional Chinese medicine treatment for DLS. Our results will provide evidence to determine whether the integrated therapy can effectively treat DLS, as well as its advantages and safety, and lay a foundation for further research. This trial is registered with ChiCTR2100050409 .